Rare Genetic Disorders: Novel Treatment Strategies and Insights Into Human Biology - Koch, Peter J.; Koster, Maranke I. (Frontiers in Genetics, 2021)
The last decade has seen a dramatic increase in innovative ideas for the treatment of genetic disorders for which no curative therapies exist. Gene and protein replacement therapies stand out as novel approaches to treat a select group of these diseases, such as certain tissue fragility disorders. Further, the advent of stem cell approaches, such as induced pluripotent stem cells (iPSC) technology, has led to the development of new methods of creating replacement tissues for regenerative medicine. This coincided with the discovery of genome editing techniques, which allow for the correction of disease-causing mutations. The culmination of these discoveries suggests that new and innovative therapies for monogenetic disorders affecting single organs or tissues are on the horizon. Challenges remain, however, especially with diseases that simultaneously affect several tissues and organs during development. Examples of this group of diseases include ectodermal dysplasias, genetic disorders affecting the development of tissues and organs such as the skin, cornea, and epithelial appendages. Gene or protein replacement strategies are unlikely to be successful in addressing the multiorgan phenotype of these diseases. Instead, we believe that a more effective approach will be to focus on correcting phenotypes in the most severely affected tissues. This could include the generation of replacement tissues or the identification of pharmaceutical compounds that correct disease pathways in specific tissues.